Benign Biliary Stricture - Outcome Analysis at Tertiary Care Hospital Quetta (Medical Forum Monthly, 2021)
Objective: To understand the varied presentation and outcome of patients with Benign Biliary Strictures.Study Design: Observational / analytical studyPlace and Duration of Study: This study was conducted at the Bolan university of Medical and Health Sciences between January 2007 and July 2019.Materials and Methods: Data was collected through review of patients charts. Malignant biliary stricture and age <15 years were excluded. The patients were divided into Endoscopic and surgery groups. Variables included demographic, etiology, type of stricture.Results: Results of surgical (Hepaticojejunostomy) and endoscopic stenting in term of hospital stay, morbidity, mortality were evaluated. Thirty-five patients were treated. 22 female and 13 male. Age ranged between 21--80 years. There were 19 patient in surgical group and 16 patients in the endoscopic group. The stricture were type1, (13) type11, (16). And type 111, (6). The outcome was good in 27 patients. 8 patients developed cholangitis. Cholangitis was more in the endoscopic group.Conclusion: The morbidity was higher in endoscopic group 37.5%. The overall excellent result was 77%. Stricture recurrence was 5.7%.The endoscopic procedure hadmore complications as compared to the surgical management.